Paintbox summer - Headley, Betty Cavanna 1909- (Westminster Press, 1949)
A seventeen-year-old girl spends a summer in Provincetown, working for Peter Hunt painting his gay peasant decorations, making a new group of friends, finding a new assurance and making a definite decision about her future.